One Year of Yoga Training Alters Ghrelin Axis in Centrally Obese Adults With Metabolic Syndrome - Yu, Angus P.; Ugwu, Felix N.; Tam, Bjorn T.; Lee, Paul H.; Lai, Christopher W.; Wong, Cesar S. C.; Lam, Wendy W.; Sheridan, Sinead; Siu, Parco M. (Frontiers in Physiology, 2018)
Introduction: Metabolic syndrome (MetS) is a multiplex cardiometabolic manifestation associated with type 2 diabetes mellitus and cardiovascular diseases. This study examined the effects of 1 year of yoga training on β-cell function and insulin resistance, and the involvement of metabolic peptides, including unacylated ghrelin (UnAG), acylated ghrelin (AG), obestatin, growth hormone (GH), and insulin, in the beneficial effects of yoga training in centrally obese adults with MetS. Methods: This was a follow up study, in which data of risk factors of MetS, physical performance tests [resting heart rate (HR), chair stand test (CS), chair sit and reach test (CSR), back scratch test (BS) and single leg stand tests (SLS)] and serum samples of 79 centrally obese MetS subjects aged 58 ± 8 years (39 subjects received 1-year yoga training and 40 subjects received no training) were retrieved for analyses. β-cell function and insulin resistance were examined by Homeostasis Model Assessment (HOMA). Circulating levels of UnAG, AG, obestatin, GH and insulin were determined by enzyme-linked immunosorbent assay using fasting serum samples. Generalized estimating equation analysis and Mann-Whitney U test were used to detect statistically significant differences between groups. Results: Waist circumference was significantly decreased after yoga intervention (control: +2%; yoga: -4%). Significant improvements in HR (control: +2%; yoga: -5%), CS (control: -1%; yoga: +24%), CSR left (control: worsen by 0.90 cm; yoga: improved by 4.21 cm), CSR right (control: worsen by 0.75 cm; yoga: improved by 4.28 cm), right side of BS (control: improved by 0.19 cm; yoga: improved by 4.31 cm), SLS left (control: -10%; yoga: +86%), and SLS right (control: -6%; yoga: +47%) were observed after 1-year yoga training. No significant difference was found between the two groups in insulin, HOMA indices and disposition index. Yoga training significantly increased circulating GH (control: -3%; yoga: +22%), total circulating ghrelin (control: -26%; yoga: +13%), and UnAG (control: -27%; yoga: +14%), whereas decreased AG (control: -7%; yoga: -33%) and obestatin (control: +24%; yoga: -29%). Conclusion: 1-year of yoga training modulated total ghrelin, UnAG, AG, obestatin and GH while exerting beneficial effects on physical functions and central obesity in adults with MetS.